Diseño de una zaranda clasificadora de material pétreo para el Municipio de Catamayo. - Jaramillo Mora, Roberto Carlos (2005)
Has been carried out the design of the machine proposed with what is sought to impel the elaboration of the same ones in our city and country. The bibliography related to the topic has been revised with the purpose of knowing the principle of operation of the sieve, of the different types of them the one has been chosen that more it is adjusted to our classification process, then it is calculated the parameters that characterize to this type of machines such an it is the case of the area of work of the sieve, width of the vibrations, vibrator, jetties among other and the other ones general as transmission of power, it structures of support, working, etc. The calculations of each one of the elements of the machine are carried out so that the resistance of the same ones it is guaranteed. The design planes are also presented to continue to carry out their construction in a reliable and effective way. He is carried out the economic and ecological valuation to determine the social and environmental impact that will have the implementation of these machines in our environment.